2015
DOI: 10.1259/bjr.20150189
|View full text |Cite
|
Sign up to set email alerts
|

Can a single isotropic 3D fast spin echo sequence replace three-plane standard proton density fat-saturated knee MRI at 1.5 T?

Abstract: Cite this article as: Pass B, Robinson P, Hodgson R, Grainger AJ. Can a single isotropic 3D fast spin echo sequence replace three-plane standard proton density fat-saturated knee MRI at 1.5 T? Br J Radiol 2015; 88: 20150189. FULL PAPERCan a single isotropic 3D fast spin echo sequence replace three-plane standard proton density fat-saturated knee MRI at 1. Objective: To assess whether a single isotropic threedimensional (3D) fast spin echo (FSE) proton density fat-saturated (PD FS) sequence reconstructed in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…For instance, a recent study by Pass et al observed reduced agreement between two independent observers for menisci and articular assessment using a 3 D fast spin echo proton density fat-saturated technique compared to the standard 2 D technique at 1.5 Tesla. However, the accuracy, sensitivity and specificity in the detection of knee pathologies were calculated using the standard 2 D protocol as the reference standard in that particular study [30]. Our study involved both quantitative and qualitative parameters to analyze the performance of both techniques and arthroscopic surgery was taken as the reference standard whenever available in a subgroup of 25 % of the patients.…”
Section: D-pdwfs 2d-pdwfs P-valuementioning
confidence: 99%
“…For instance, a recent study by Pass et al observed reduced agreement between two independent observers for menisci and articular assessment using a 3 D fast spin echo proton density fat-saturated technique compared to the standard 2 D technique at 1.5 Tesla. However, the accuracy, sensitivity and specificity in the detection of knee pathologies were calculated using the standard 2 D protocol as the reference standard in that particular study [30]. Our study involved both quantitative and qualitative parameters to analyze the performance of both techniques and arthroscopic surgery was taken as the reference standard whenever available in a subgroup of 25 % of the patients.…”
Section: D-pdwfs 2d-pdwfs P-valuementioning
confidence: 99%
“…The images obtained in 3D sequences have high tissue signal intensity, good signal-to-noise ratio (SNR), high image resolution, and fewer volume averaging artefacts. Unfortunately, the image acquisition time in 3D sequences is usually longer than in 2D sequences, which can potentially increase the risk of movement artefacts and cause the sequence to be repeated (35).…”
Section: Introductionmentioning
confidence: 99%
“…Particular interest in the possibility of image reconstruction can be observed in human medicine. Although it was mainly used in research with the application of high-field devices (16,21,30,34,35,39,47), its use has also been described with low-field systems in operation (31).…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors question the real value of 3D FSE sequences for the diagnosis of meniscal and cartilaginous lesions in 1.5 T MRI scanners, those same authors acknowledge their value in providing better characterization of the injuries and improving diagnostic reliability as well as in reducing the total examination time ( 7 ) . Other researchers, also using 1.5 T scanners, obtained results similar to or even better, in some cases, than those obtained with 2D sequences for the detection of knee injuries ( 8 ) .…”
mentioning
confidence: 99%
“…( 8 ) and Pass et al. ( 7 ) , both of whom also employed 1.5 T scanners, presented conflicting results regarding the substitution of volumetric sequences for the traditional 2D protocol in knee evaluations. However, both of those studies emphasized the clinical value of 3D sequences in allowing reformatting in any plane and representing a quicker option for patients in pain or who suffer from claustrophobia ( 2 ) .…”
mentioning
confidence: 99%